A study on soil arching effect of anti-slide pile considering different pile arrangements - Shangguan, Yunlong; Xue, Dongsheng; Wang, Gang; Li, Dongxin; Bao, Shuochao; Wang, Wenhua (Frontiers in Earth Science, 2023)
Among the methods of landslide treatment, anti-slide piles are an effective measure. The soil arching effect cannot be ignored in the design of anti-slide piles, which has a significant impact on the supporting. Based on the field investigation, this paper selects the Xinyan landslide in Yanbian area of Jilin Province and uses Flac-3D to build a numerical model to simulate its soil arching effect with different pile arrangements. The simulation results show that the pile arrangement has a significant influence on the soil arching effect. When arranging piles in parallel, the soil arches between the front and rear rows of piles are distributed parallel to each other. When arranging piles in quincunx-shape, the soil arches between the rear rows of piles are the same as when laying piles in parallel. The soil between the piles flows around once when the piles are laid out in parallel, while it flows around twice when the piles are laid out in a quincunx-shape. The latter has better support than the former.